2010
DOI: 10.1111/j.1471-0528.2009.02434.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of urinary soluble endoglin in the diagnosis of pre‐eclampsia: comparison with soluble fms‐like tyrosine kinase 1 to placental growth factor ratio

Abstract: Objective Endoglin, an anti-angiogenic glycoprotein expressed on endothelial cells, has been proposed recently as a biomarker of pre-eclampsia (PE). Given that PE is characterised by an imbalance of angiogenic factors, we sought to determine the clinical utility of urinary soluble endoglin, relative to the soluble fms-like tyrosine kinase 1 to placental growth factor (PlGF) ratio, in the diagnosis of PE during gestation.Design Prospective observational cohort.Setting Tertiary referral university hospital.Popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
1
10
0
2
Order By: Relevance
“…The Gli1 knockout animals in our colony developed normally and were fertile when they reached adulthood, consistent with the original observation [24]. At the time of birth, the reproductive organs in Gli1 and Gli2 knockout newborns were indistinguishable from their respective wild-type littermates (Fig.…”
Section: Effects Of Loss Of Gli1 or Gli2 On Fetal Testessupporting
confidence: 65%
“…The Gli1 knockout animals in our colony developed normally and were fertile when they reached adulthood, consistent with the original observation [24]. At the time of birth, the reproductive organs in Gli1 and Gli2 knockout newborns were indistinguishable from their respective wild-type littermates (Fig.…”
Section: Effects Of Loss Of Gli1 or Gli2 On Fetal Testessupporting
confidence: 65%
“…Of note in our study population 24 h urine samples all showed increased levels of protein excretion over 300 mg. In any case other urinary biomarkers, such as urinary soluble endoglin [23] and inhibin A [24] which have been shown to be elevated in women with PE, might be more favorable for further investigation. Furthermore proteomics-based characterization of urine samples is a very promising approach that has been shown to be of value in accurately diagnosing PE and discriminating it from other hypertensive proteinuric disease [25].…”
Section: Commentmentioning
confidence: 94%
“…For pregnancies that have a high risk to develop preeclampsia, based on clinical parameters or sFlt-1 and PIGF, [3][4][5][6] homebased self-monitoring of BP in combination with the adipsin strip test seems to be a feasible approach for early detection of the preeclampsia onset. Because of the easiness of the test conduction and result interpretation, it requires only a brief education for the test conductor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that altered concentration of soluble fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PIGF) can predict the occurrence of preeclampsia weeks before the appearance of the clinical symptoms. [3][4][5][6] Uterine artery Doppler studies that assess the pulsability index reveal increased uterine vascular resistance well before the preeclampsia clinical signs arise.…”
mentioning
confidence: 99%
See 1 more Smart Citation